2013
DOI: 10.7732/kjpr.2013.26.6.726
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Contents of Ginsenoside Due to Boiling Process of Panax ginseng C.A. Mayer

Abstract: The purpose of the study was to determine a method to use fresh white Korean ginseng in the form of higher intake of medicinal components. Decoction was made at 70℃ and 90℃ in different intervals of time. HPLC (DAD) system was employed to monitor the ginsenosides content in the decoctions and the components were identified by comparing the retention time with that of reference compounds. However, decoction made at 70℃ in 72 hrs possessed higher amount of total ginsenosides (209.6 μg/mL) content where considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There are several different methods for administering ginseng in TKM. P. Ginseng has traditionally been made into a beverage by boiling its decoction in water for several hours (13), but solvents, such as water and alcohol, have recently been employed to concentrate the ginseng extract (14). These oral intake methods for ginseng have been proven to be clinically effective and safe (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…There are several different methods for administering ginseng in TKM. P. Ginseng has traditionally been made into a beverage by boiling its decoction in water for several hours (13), but solvents, such as water and alcohol, have recently been employed to concentrate the ginseng extract (14). These oral intake methods for ginseng have been proven to be clinically effective and safe (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…cultivated ginseng [3], and proteomic analysis revealed that wild ginseng contains higher levels of amino acids, amino acid-related enzymes and proteins, and derivatives than cultivated ginseng [4]. Traditionally, P. ginseng is used in the decoction form and is decocted with boiling water for a certain number of hours and prepared as a drink [5]. More recently, ginseng concentrates, extracted using water or alcohol, are also used [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was originally developed under the name of 'Aqua-acupuncture' in the 1950s in China [10]. Aqua-acupuncture uses Traditionally, P. ginseng is used in the decoction form and is decocted with boiling water for a certain number of hours and prepared as a drink [5]. More recently, ginseng concentrates, extracted using water or alcohol, are also used [6].…”
Section: Introductionmentioning
confidence: 99%